The Contribution Teaching Factory On Practical Learning Process, Production Process And Vocational School Quality - Kristanto Kristanto; Tri Kuat; Bambang Noor (Journal Of Social Science (JoSS), 2023)
The purpose of the research is; (1) to describe teaching factory implementation; (2) to describe contribution of teaching factory on practical learning; (3) to describe contribution of teaching factory on production process; (4) to describe contribution of teaching factory on vocational school quality. This research employed qualitative method with case study approach. The research was done in SMK Muhammadiyah1 Sukoharjo, and the research subject is headmaster, teachers, and students. The data collection technique is taken by observation, interview and documentation with qualitative analysis data followed data reduction, data display and conclusion drawing. The result of the research shows that; (1) teaching factory implementation runs well and the teaching factory in the school is more modern and it has become the technopark as reference of other vocational schools’ teaching factory; (2) teaching factory learning contributes significantly on practical learning; (3) teaching factory learning contributes production process; (4) and teaching factory learning contributes vocational school quality in SMK Muhammadiyah 1 Sukoharjo.